A 6-month, double-blind, placebo-controlled, randomized trial to evaluate the effect of Eurycoma longifolia (Tongkat Ali) and concurrent training on erectile function and testosterone levels in androgen deficiency of aging males (ADAM). (March 2021) - Leitão, Alice Erwig; Vieira, Melissa Carvalho de Souza; Pelegrini, Andreia; da Silva, Edson Luiz; Guimarães, Adriana Coutinho de Azevedo
Highlights: Eurycoma longifolia and the practice of concurrent training for 6 months significantly improved the erectile function of men with androgen deficiency. Eurycoma longifolia increased testosterone levels in almost 50 % of study participants. Testosterone level was correlated with function in domains of men's sexual health. Abstract: Background: Androgen deficiency of aging males (ADAM) largely manifests as sexual symptoms. Erectile dysfunction is one of the most common symptoms of ADAM. Aim: To ascertain the effect of concurrent training and supplementation with Eurycoma longifolia on erectile function and testosterone levels in men with ADAM, and the association of erectile function with levels of total testosterone. Methods: 6-month, randomized, double-blind, placebo-controlled four-arm clinical. 45 men (47.38 ± 5.03 years) were randomized into 4 groups (G1: control + placebo; G2: control + Eurycoma longifolia ; G3: concurrent training + placebo; G4: concurrent training + Eurycoma longifolia ). 22 received a 200 mg supplement of Eurycoma longifolia and 23 underwent the intervention with concurrent training, 3 times a week for 60 min at progressive intensity. Outcomes: International Index of Erectile Function (IIEF-5), Aging Male Scale (AMS) and total testosterone. Results: Erectile function demonstrated improvements in both interventions; however, the most significant results were obtained by men allocated to concurrent training + Eurycoma longifolia . Clinical implications: A 200 mg supplement of Eurycoma longifolia and the practice of concurrent training for 6 months significantly improved the erectile function of men with ADAM. Strengths & limitations: The study's design stands out as a strength, in addition to the six-month intervention. The main limitation is the study not having groups that used only Eurycoma longifolia and only concurrent training. Conclusion: The combination of Eurycoma longifolia and concurrent training improved erectile function and increased total testosterone levels in men with ADAM.